Early to Late VSV-G Expression in AcMNPV BV Enhances Transduction in Mammalian Cells but Does Not Affect Virion Yield in Insect Cells - Jorge Alejandro Simonin; Franco Uriel Cuccovia Warlet; María del Rosario Bauzá; María del Pilar Plastine; Victoria Alfonso; Fernanda Daniela Olea; Carolina Susana Cerrudo; Mariano Nicolás Belaich (Vaccines)
Background/Objectives: Baculoviruses represent promising gene delivery vectors for mammalian systems, combining high safety profiles with substantial cargo capacity. While pseudotyping with vesicular stomatitis virus G-protein (VSV-G) enhances transduction efficiency, optimal expression strategies during the Autographa californica multiple nucleopolyhedrovirus (AcMNPV) infection cycle remain unexplored. This study investigates how VSV-G expression timing affects pseudotype incorporation into budded virions (BVs) and subsequent transduction efficacy. Methods: Three recombinant AcMNPV constructs were generated, each expressing VSV-G under distinct baculoviral promoters (ie1, gp64, and p10) and GFP via a CMV promoter. VSV-G incorporation was verified by Western blot, while transduction efficiency was quantified in mammalian cell lines (fluorescence microscopy/flow cytometry) and rat hind limbs. Viral productivity was assessed through production kinetics and plaque assays. Results: All the pseudotyped viruses showed significantly enhanced transduction capacity versus controls, strongly correlating with VSV-G incorporation levels. The p10 promoter drove the highest VSV-G expression and transduction efficiency. Crucially, BV production yields and infectivity remained unaffected by VSV-G expression timing. The in vivo results mirrored the cell culture findings, with p10-driven constructs showing greater GFP expression at low doses (104 virions). Conclusions: Strategic VSV-G expression via very late promoters (particularly p10) maximizes baculoviral transduction without compromising production yields. This study establishes a framework for optimizing pseudotyped BV systems, demonstrating that late-phase glycoprotein expression balances high mammalian transduction with preserved insect-cell productivity—a critical advancement for vaccine vector development.